IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DAN PROFIL PELAJAR RAHMATAN LIL ALAMIN (PPRA) TEMA KEARIFAN LOKAL - Elma Kumala; Ida Fauziatun Nisa’; Usman Roin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Education serves as a method of passing down cultural legacy, knowledge, and abilities to the following generation. The curriculum is a vital instrument in achieving educational objectives.